Effects of vitamin D signaling in cardiovascular disease: centrality of macrophage polarization - Fliri, Anton; Kajiji, Shama (Frontiers in Cardiovascular Medicine, 2024)
Among leading causes of natural death are cardiovascular diseases, cancer, and respiratory diseases. Factors promoting illness are aging, stress, chronic inflammation, environmental factors, declining autophagy, and endocrine abnormalities including insufficient levels of Vitamin D. Prompted by inconclusive clinical outcomes of Vitamin D supplements in cardiovascular diseases, we have employed a spectral clustering methodology to examine roles of Vitamin D’s genomic and non-genomic signaling in disease. Results of this investigation showed that (1) Vitamin D regulates multiple reciprocal feedback loops including p53, macrophage autophagy, nitric oxide, and redox-signaling and that (2) these regulatory schemes are involved in over 2000 diseases. Furthermore, the balance between genomic and non-genomic signaling by Vitamin D affects autophagy regulation of macrophage polarization in tissue homeostasis. These findings provide a deeper understanding of how interactions between genomic and non-genomic signaling affect Vitamin D pharmacology and offer opportunities for increasing efficacy of vitamin-D centered treatment of cardiovascular disease and healthy lifespans.